Functional Conservation of Regulatory Elements in the pdx-1 Gene: PDX-1 and Hepatocyte Nuclear Factor 3β Transcription Factors Mediate β-Cell-Specific Expression - Marshak, Sonya (American Society for Microbiology, 2000)
The PDX-1 transcription factor plays a key role in pancreatic development and in the regulation of the insulin gene in the adult β cell. As its functions appear to be similar in humans and mice, we analyzed the functional conservation of homologous sequences important for the maintenance and the cell-specific regulation of the pdx-1 gene. Apart from the proximal promoter region, three highly homologous (PH1 to PH3) sequences were apparent in the human and mouse 5′ flanking regions of the gene. By transient transfections in β and non-β cells, we show that mainly PH1 and PH2 preferentially confer β-cell-specific activation on a heterologous promoter. DNase I footprinting and binding analyses revealed that both bind to and are transactivated by hepatocyte nuclear factor 3β (HNF-3β). Furthermore, the PH1 enhancer element also binds the PDX-1 transcription factor itself, which acts cooperatively with adjacent HNF-3β to regulate its transcriptional potency. This finding suggests a possible autoregulatory loop as a mechanism for PDX-1 to control its own expression.